2012
DOI: 10.1016/j.aat.2012.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Development of acute ischemic stroke in a patient with acute respiratory distress syndrome (ARDS) resulting from H1N1 pneumonia

Abstract: Pneumonia due to H1N1 infection is now very common. We report a case of ischemic stroke which arose subsequently to H1N1 influenza. The patient was a female who developed acute respiratory distress syndrome (ARDS) after H1N1 influenza, was ventilated as per standard protocol and started treatment with oseltamivir. When sedation was stopped during weaning from the ventilator, she was found to have left hemiparesis resulting from multiple infarctions in the brain. Contrary to thrombocytosis usually seen in acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…These apparently disparate diseases share physiological and clinical associations. Burad et al ( 2012 ) found that acute respiratory syndrome in pneumonia patients leads to strong systemic ischemia that may in turn develop into acute encephalopathy. This finding has been further confirmed in a very large (5.6 million cases) epidemiological risk factor study of the group of Bell in the US (Rincon et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…These apparently disparate diseases share physiological and clinical associations. Burad et al ( 2012 ) found that acute respiratory syndrome in pneumonia patients leads to strong systemic ischemia that may in turn develop into acute encephalopathy. This finding has been further confirmed in a very large (5.6 million cases) epidemiological risk factor study of the group of Bell in the US (Rincon et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…One case of multiple strokes occurred in a young woman with disseminated intravascular coagulation who was critically ill. 72 The other case occurred in a 50-year-old woman with ARDS secondary to influenza A(H1N1) who developed multiple strokes in the territory of the right middle cerebral artery. 73 There may be indirect evidence of an association between influenza and CVAs, but data from influenza vaccination and neuraminidase inhibitors are conflicting. 74,75 One case-control study in France found that the risk of stroke was reduced in subjects vaccinated in that year compared to those not vaccinated (OR 0.50, 95% CI 0.26-0.94).…”
Section: Strokementioning
confidence: 99%
“…A total of 115 articles were initially retrieved, but eleven of them were eliminated according to our exclusion criteria. Finally, considering our inclusion criteria, only 104 articles (1636 patients) were included and divided into two groups, according to the origin of neurological complications: influenza vaccine‐related (287 patients) or viral infection‐related (1349 patients) (Tables S1 and S2) . The main characteristics of patients are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%